Distribution and ecological risk assessment of heavy metals in surface sediments of a typical restored mangrove–aquaculture wetland in Shenzhen, China. Issue 2 (30th November 2017) - Feng, Jianxiang; Zhu, Xiaoshan; Wu, Hao; Ning, Cunxin; Lin, Guanghui
Abstract: The restoration of wetlands has attracted the attention in different countries. Restored coastal wetlands, especially urban wetlands, are sensitive to external pressures. Thus, it is necessary to evaluate the efficiency of the restoration of coastal wetlands, which benefits their management and functional maintenance. In this study, a restored mangrove-aquaculture system in Waterlands Resort at Shenzhen was selected for analysis. The distribution and ecological risk assessment of heavy metals in surface sediments were investigated. The results showed that restoration could effectively decrease the heavy metal concentrations in the sediment, while the restored mangrove posed a moderate ecological risk. Most of the heavy metal concentrations were higher during the dry season compared with the wet season. In addition, during the whole investigation, the sediment quality remained failed to achieve the marine sediment criteria required for aquaculture in China. Highlights: Distribution and ecological risk of heavy metals in a restored mangrove-aquaculture system were analyzed. Restoration effectively decreased most of the heavy metals concentrations in the sediment of the restored wetland. A moderate ecological risk was determined in sediment of the restored mangrove.